That mighty "pantun" river and its tributaries - Ming, Ding Choo (Wacana, Journal of the Humanities of Indonesia, 2010)
Known as pantun to the Malays in Brunei, Malaysia, Pattani, Riau, Singapore, and Southern Phillipines, it is called peparikan to the Javanese, sesindiran to the Sundanese and many other different names in different ethnic groups in the different parts of the Indo-Malay world, which is made up of Brunei, Indonesia, Malaysia, Singapore, Pattani in southern Thailand, and Mindanao in the southern Philippines. In almost every settlement that sprang up along the major rivers and tributaries in the Indo-Malay world, the pantun blend well with their natural and cultural surroundings. In this article, the geographical extent of the pantun family in the Indo-Malay world is likened to a mighty river that has a complex network of tributaries all over the Indo-Malay world. Within the Indo-Malay world, it is the movement of the peoples help the spread of pantun from one area to the other and makes it an art form of immensely rich and intricate as can be seen from the examples given.